الهندسة المالية الإسلامية كمدخل لتطوير الصيرفة الإسلامية: دراسة التجربة السودانية - نجار، حياة; بورمة، هشام (جامعة الزرقاء - كلية الاقتصاد والعلوم الإدارية, 2017)
أعطي ظهور الهندسة المالية خطوط ابتكارات عديدة ومتنوعة، هذه الابتكارات شكلت النواة الأولى التي اعتمد عليها علماء وخبراء المصرفية الإسلامية في التخلص من منتجات المالية التقليدية الربوية واستبدالها بأخرى توافق أحكام الشريعة الإسلامية؛ هذه المنتجات تلقى وتحظى بقبول الأفراد والمجتمع على حد سواء، لما يميزها من كفاءة اقتصادية ومصداقية شرعية. توفر الهندسة المالية الإسلامية مزايا عديدة يمكن أن تستفيد منها المؤسسات المالية الإسلامية، وما عملية التصكيك إلا واحدة من إفرازات الهندسة المالية الإسلامية، حيث أثبتت نجاعتها ونجاحها في الكثير من البلدان الإسلامية على غرار ماليزيا، باكستان والسودان، غير أنه وبسبب الأحداث الاقتصادية المتسارعة والتقلبات المالية التي صاحبتها أزمات مالية عالمية، جعلت خبراء وفقهاء الصيرفة الإسلامية في تحد وبحث دائم لمسايرة تلك التغيرات من أجل وإرضاء وإشباع حاجات العملاء دون تجاوز الخطوط الشرعية التي يقوم عليها العمل المالي والمصرفي الإسلامي، وفعلا أظهرت الصناعة المالية الإسلامية كفاءة في تحد الأزمات والتصدي لها؛ من هنا كانت إشكاليتنا التي تبحث دور الهندسة المالية الإسلامية في تطوير الصيرفة الإسلامية. The emergence of financial engineering has given rise to many and varied innovations. These innovations formed the first nucleus upon which Islamic banking scholars and experts relied on the elimination of traditional riba-based financial products and replacing them with Shari'ah-compliant products. These products are accepted and accepted by individuals and society alike. economic credibility and legitimacy of efficiency. Islamic financial architecture offers many advantages can benefit from Islamic financial institutions, and the securitization process, but one of the secretions of the Islamic financial engineering, where proven and successful in many Islamic countries like Malaysia, Pakistan and Sudan, but because of the rapid financial and economic fluctuations events accompanied by a global financial crisis, it has made experts and scholars of Islamic banking in defiance of a permanent research in order to keep pace with these changes in order to satisfy customers' needs and satisfy the legitimate lines without exceeding the underlying Islamic finance and banking, and actually has shown T Islamic finance industry in the efficiency of the challenge and crisis response; from here was Ashkalatna looking on the role of Islamic financial engineering in the Islamic financial industry development.
Keywords: المصارف الإسلامية -- الصيرفة الإسلامية -- المنتجات المالية -- الهندسة المالية -- السودان